2020
DOI: 10.3389/fphar.2020.576887
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Membranes as Key Targets for the Pharmacological Actions of Ginsenosides

Abstract: In this review, we will focus on the activity of ginsenosides on membranes and their related effects, from physicochemical, biophysical, and pharmacological viewpoints. Ginsenosides are a class of saponins with a large structural diversity and a wide range of pharmacological effects. These effects can at least partly be related to their activity on membranes which results from their amphiphilic character. Some ginsenosides are able to interact with membrane lipids and associate into nanostructures, making them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…On the other hand, the mechanism of action of steroids as antibacterial agents is actually by disruption of bacterial cell membranes (Jannah et al, 2017). Lastly, saponins causes increase in the permeability of cell membranes and thus inhibit bacterial growth and render cells unstable which leads to cell lysis (Verstraeten et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the mechanism of action of steroids as antibacterial agents is actually by disruption of bacterial cell membranes (Jannah et al, 2017). Lastly, saponins causes increase in the permeability of cell membranes and thus inhibit bacterial growth and render cells unstable which leads to cell lysis (Verstraeten et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some ginsenosides inhibit drug efflux pumps, which can enhance the activity of conventional chemotherapeutic agents. For a review on this topic, please refer to ( Verstraeten et al, 2020 ).…”
Section: Targeting Membrane Cholesterol and Cholesterol-enriched Doma...mentioning
confidence: 99%
“…A few decades ago, possible interaction between natural saponins (quillaja saponins) and proteins (casein and soy proteins) and their influence on blood lipids, particularly low-density lipoprotein (LDL) cholesterol, was established [53]. Recently, it has been shown that Ginseng saponins, ginsenosides, bind to plasma lipid membranes to exert their pharmacological actions through the modulation of essential membrane proteins and the reorganisation of lipid bilayers [54]. As ginsenosides suppress cell proliferation, induce apoptosis, and inhibit efflux pumps, these saponins could be considered as candidates for anticancer and antimicrobial drug development [55].…”
Section: Saponinsmentioning
confidence: 99%